2004
DOI: 10.1158/1078-0432.ccr-03-0707
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle–Dependent Antagonistic Interactions between Paclitaxel and γ-Radiation in Combination Therapy

Abstract: Purpose: The promising clinical activity of paclitaxel, a naturally occurring antimicrotubule agent, has promoted considerable interest in combining this drug with radiation therapy, but it remains unclear whether such a combination would increase the therapeutic efficacy. This study is to assess the potential interactions between paclitaxel and ␥-radiation against human tumor cells in vitro.Experimental Design: Paclitaxel and ␥-radiation were administered in three different sequences designated as preradiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
8
35
0
Order By: Relevance
“…The human beast cancer BCap37 cell line has been used as a wellcharacterized cell model in our previous studies for the evaluation of taxane-containing combination therapy (19,20,(30)(31)(32). This ERÀ cell line is very sensitive to paclitaxel and docetaxel in both mitotic arrest and apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human beast cancer BCap37 cell line has been used as a wellcharacterized cell model in our previous studies for the evaluation of taxane-containing combination therapy (19,20,(30)(31)(32). This ERÀ cell line is very sensitive to paclitaxel and docetaxel in both mitotic arrest and apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 0.5 Â 10 5 to 1 Â 10 5 cells were plated onto microscope slides using the Cytospin 3 cell preparation system. As described previously (30), slides were air dried and fixed in absolute methanol before Giemsa staining. Slides from three independent experiments were examined and photographed using bright-field microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that the CDK1/cyclin B1 complex plays a critical role during the G 2 phase. During the G 2 phase, CDK1 forms a heterodimeric complex with cyclin B1 and remains inactive, the CDK1/cyclin B1 complex could be activated by CDK7 (33). The up-regulation process of CDK1 and cyclin B seem to be necessary to block the cell at G 2 -M phase (34).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In addition, our recent studies indicated that IkBa/NFkb signaling pathway might play a critical role in the mediation of paclitaxel-induced apoptotic cell death. 21,22 We performed Western blotting of BCap37 cell extracts to examine the potential altered expression of a number of regulatory proteins that could contribute to the activity of paclitaxel in inducing cell cycle arrest and apoptosis.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%